Preparation of gold and gold-silver alloy nanoparticles for enhancement of plasmonic dye-sensitized solar cells performance - Al-Azawi, M. A. (Elsevier Ltd, 2016)
A two-step method was applied to obtain gold-silver alloy nanoparticles (Au-Ag alloy NPs). First, Au and Ag colloids with average particle sizes of 14.80 and 8.47nm, respectively, were synthesized by pulsed laser ablation of pure metallic targets immersed in ethanol, subsequent mixing, and re-irradiation of individual Au and Ag colloids (volume ratio of 4:1). In this study, a dense layer of porous titanium dioxide (TiO2) film with a thickness of ~11μm was deposited directly on the central area of the conductive face of a fluorine tin oxide (FTO) glass by blade doctor method. A specific amount of N719 dye molecules with and without the plasmonic-metal nanoparticles (NPs) was mixed, incorporated into the porous TiO2 film, and used as photoanode to fabricate dye-sensitized solar cells (DSSCs). The optical and structural properties of the prepared photoanodes before their application to DSSCs were investigated. The photocurrent density-voltage and external quantum efficiency characteristics of the DSSCs fabricated with these photoanodes were also analyzed and discussed. The experimental results confirmed the plasmonic enhancement effects on the performance of DSSCs, which indicated that cells loaded with the plasmonic-metal NPs yielded larger enhancement. The plasmonic effect of the Au-Ag alloy NPs significantly enhanced the broadband light absorption of dye molecules. The best cell was achieved using the photoanode loaded with Au-Ag alloy NPs, exhibiting a power conversion efficiency of 5.81%, which was ~8.4% and 52.1% higher than that of the DSSCs with Au NPs and the reference cell, respectively.